A utilidade do reporte financeiro para as tomadas de decisão internas nos municípios portugueses - Nogueira, Sónia P. (2013)
The aim of this study is to analyse the perceptions of internal users regarding the usefulness of financial reporting in the context of decision-making of Portuguese Local Administration. To do this, a survey questionnaire to all municipalities’ decision-makers (both technical and political) was carried out. The main findings suggest that usefulness of municipalities’ financial reporting, in its current form and content, is high. Nevertheless, this usefulness would increase with the introduction of other information apart from the one that is currently required to disclose. In general, the two different groups of decision-makers – technical and political – have a slightly different behaviour with respect to the usefulness attributed to municipalities’ financial reporting, within the context of internal decision-making. The technical decision-makers assign more usefulness than politicians. Additionally, there is a preference, albeit slight, by all users for cash-based budgetary information, although accrual-based information (patrimonial and cost accounting) also reveals a high usefulness.